STRATEGI PENGELOLAAN TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH DI KOTA PEKANBARU - Indriani Zulfan; Darwis Darwis; Sofia Anita (Program Pascasarjana Universitas Riau, 2021)
The existence of landfill as final waste management was used by some people to live near a landfill and acquire a livelihood. This kind of situation could influence health and social condition, also environment as the impact from landfill. The aim of this research to analyze the condition of existing landfill in Mandau Sub-district, the negative and positive impact and the modeling of landfill based on community. The research was quantitative and qualitative used survey method with interview, questionnaires and observational directly. The sampling technique was purposive sampling and the participants of this study were consist of 30 scavengers and 20 families who lived are limited to 300 meter from landfill and they were interviewed accidentally by researcher. This research also involved the governments in supporting data collection. The data were analyzed and presented in the form of descriptions. The result obtained the current landfills condition were not feasible if it still used the open dumping method with a service period of up to 9 years 2 months. The negative impact caused by landfill activity also affected to scavengers ' health. The positive impact was the emergence of a job which could produce income for family economic. Landfill modelling which could be applied was 3R + 1P concept according to Ministerial Regulation (Trash Bank and Integrated Waste Management), this concept was socialized to community..